Monitoreo de la calidad de agua del Río Malacatos, tramo comprendido desde los Dos Puentes hasta el sector de Sauces Norte. - Maldonado Mendieta, Galo Antonio (2014)
Compare and develop three methodologies of water quality analysis to evaluate surface sources, the present titling ending project will help to establish appropriate management practices in rivers and have an idea of the critical parameters to be monitored to maintain an acceptable quality control of water that we are using. Was determined a monitoring network of nine points along the study reach, in three samplings at different times of year. In developing the Water Quality Index (IQA-MC) to the river Malacatos, length comprised from Dos Puentes until arriving at Sauces Norte sector, it is intended to classify on a scale of 0 to 100 water representative quality, according to the characterization of evaluated constituent. As a result is obtained an average of 47 (dimensionless value) classifying it as highly contaminated water, occur with most influence the following terms: organic concentration, fecal contamination, aesthetic aspects presence of total suspended solids and total dissolved solids, nutrients and heavy metals such as lead, mercury, arsenic and cadmium.